Analysis of Risk Factors for Chronic Energy Deficiency (CED) among Pregnant Women - Putri Ayu Tomu; Sunarto Kadir; Chairunnisah J. Lamangantjo (GLOBAL HEALTH SCIENCE GROUP, 2025)
Chronic Energy Deficiency (CED) is a condition of inadequate energy intake that can have negative impacts on the health of pregnant women and fetuses, and increase the risk of pregnancy complications. Several factors can influence the occurrence of CED, including carbohydrate intake, protein intake, fat intake, maternal age, family income, pregnancy spacing, and food availability. A better understanding of these risk factors is expected to help in efforts to mitigate and manage CED in pregnant women. This study aims to identify the risk factors for CED among pregnant women at Limboto Health Center. This study employed a cross-sectional design. The sample consisted of 100 pregnant women at the Limboto District Health Center, selected using simple random sampling. Data were collected using MUAC (Mid-Upper Arm Circumference) measurements, 24-hour recall forms, and questionnaires. The research instruments used in this study have been validated (Sig 2-tailed < 0.05) and proven reliable (Cronbach's Alpha > 0.7), confirming their suitability for use. Data analysis used chi-square to examine the relationships between variables and logistic regression to identify the most influential variables. Statistical analysis revealed significant relationships between carbohydrate intake (p = 0.002), protein intake (p = 0.003), fat intake (p = 0.002), age (p = 0.000), family income (p = 0.009), pregnancy spacing (p = 0.004), and food availability (p = 0.000). Fat intake had the greatest influence on Chronic Energy Deficiency (CED) (Exp (B) = 143.372). Factors such as carbohydrate intake, protein intake, fat intake, age, family income, pregnancy spacing, and food availability are associated with the occurrence of CED among pregnant women. Therefore, efforts to prevent and manage CED in pregnant women need to consider these factors, particularly in improving nutrient intake to support the health of both mother and fetus.